Palaeomacrosemius thiollieri, gen. et sp. nov., a new Macrosemiidae (Neopterygii) from the Upper Jurassic of the Solnhofen Archipelago (Germany) and Cerin (France), with a revision of the genus Macrosemius. Issue 5 (2nd September 2016) - Ebert, Martin; Lane, Jennifer A.; Kölbl-Ebert, Martina
ABSTRACT: We describe Palaeomacrosemius thiollieri, gen. et sp. nov., a new genus of Macrosemiidae (Neopterygii: Ginglymodi), from the Upper Jurassic (late Kimmeridgian to early Tithonian) of the Solnhofen Archipelago (Germany) and Cerin (France). Palaeomacrosemius, gen. nov., is characterized primarily by the following features: presence of vertical scale rows that do not dichotomize dorsal to the lateral line (unlike members of the genus Macrosemius Agassiz); a long dorsal fin with 32–33 dorsal fin rays; and a smaller scale-free area immediately ventrolateral to the dorsal fin compared with Macrosemius . Small, hook-like spines located on the posterolateral border of the principal dorsal fin rays may have functioned in reproductive behavior. We also review the currently known species of Macrosemius ( M . rostratus Agassiz and M . fourneti Thiollière) from the Upper Jurassic plattenkalk of southern Germany and Cerin, France. Macrosemius rostratus, which we here restrict to the German plattenkalk basins of Eichstätt and Solnhofen (Tithonian above the eigeltingense horizon), is mainly characterized by the presence of 37–39 dorsal fin rays, which are very long in adult specimens. Macrosemius fourneti is mainly characterized by the presence of 34–35 dorsal fin rays, which are broader in the posterior part of the fin. Although M . fourneti was previously known only from Cerin, France, we here describe it for the first time from the older plattenkalk of Brunn (southern Germany, late Kimmeridgian). Citation for this article: Ebert, M., J. A. Lane, and M. Kölbl-Ebert. 2016. Palaeomacrosemius thiollieri, gen. et sp. nov., a new Macrosemiidae (Neopterygii) from the Upper Jurassic of the Solnhofen Archipelago (Germany) and Cerin (France), with a revision of the genus Macrosemius . Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1196081. http://zoobank.org/urn:lsid:zoobank.org:pub:414EFC70-C0FC-4CE7-919C-20ACB28A709D